TEACHING MATHEMATICS AT UNIVERSITY. CREATING WORKBOOKS - Irina G. Popova; Anna V. Shishova; Victor L. Tsyganov (Высшее образование в России)
Aiming at improving the quality of teaching mathematics at higher educational institutions authors discuss one of the instruments - workbook complexes which can beimplemented as an element of educational and methodical complex as well as one of the assessment means.